The contribution of motivation and stakeholder support in internship programs to work readiness and entrepreneurial readiness: A SEM-PLS analysis - Janani Janani; Hasan Maksum; M. Giatman; Rifdarmon Rifdarmon; Lasyatta Syaifullah (Journal Industrial Servicess, 2026)
Vocational high school graduates consistently record the highest open unemployment rate among all education levels, indicating a persistent gap between vocational education outcomes and labor market demands. This study examines the contribution of student motivation and stakeholder support from family, school, and industry to work readiness and entrepreneurial readiness, with internship programs as the mediating variable. A quantitative causal-associative design was employed with a cross-sectional approach. A total of 190 respondents were selected from a population of 307 using proportionate stratified random sampling, representing students, supervising teachers, parents, and industry supervisors. Data were collected via validated Likert-scale questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Results confirmed all eight hypothesized mediation paths. Internship programs strongly and significantly predicted both work readiness and entrepreneurial readiness, functioning as the primary mediator that transforms motivation and stakeholder support into concrete career readiness outcomes. School support emerged as the dominant contributor to internship program quality, followed by parental support, industry support, and student motivation. The model explained more than eighty percent of the variance in internship program implementation. These findings provide empirical evidence that improving vocational graduate career readiness requires coordinated investment in internship program quality, teacher capacity building, and entrepreneurship integration, particularly in the agribusiness sector.